Life After Business Failure - Ucbasaran, Deniz; Shepherd, Dean A.; Lockett, Andy; Lyon, S. John (Journal of Management, 2013)
Where there is uncertainty, there is bound to be failure. It is not surprising, therefore, that many new ventures fail. What happens to entrepreneurs when their business fails? People hear of highly successful entrepreneurs extolling the virtues of failure as a valuable teacher. Yet the aftermath of failure is often fraught with psychological, social, and financial turmoil. The purpose of this article is to review research on life after business failure for entrepreneurs, from the immediate aftermath through to recovery and re-emergence. First, the authors examine the financial, social, and psychological costs of failure, highlighting factors that may influence the magnitude of these costs (including individual responses to managing these costs). Second, they review research that explains how entrepreneurs make sense of and learn from failure. Finally, the authors present research on the outcomes of business failure, including recovery as well as cognitive and behavioral outcomes. They develop a schema to organize extant work and use this as a platform for developing an agenda for future research.